Prevenção à violência sexual infantojuvenil nos serviços socioassistenciais no interior do Tocantins - Rocha, Noemi Medeiros (Universidade Federal do Tocantins, 2024)
In the present paper, we propose to discuss how the prevention of sexual violence against children and adolescents is carried out in a small municipality located in the state of Tocantins, focusing on the analysis of how social assistance services Centro de Referência de Assistência Social - CRAS and Centro de Referência Especializado de Assistência Social - CREAS have been working with the prevention of this type of violence and the main challenges that permeate this operation. The relevance of such research is due to the notion that sexual violence against children and adolescents is characterized as an expression of a social matter, being appointed by the model of exploitation and domination that comes with capitalism and economic liberalism. Therefore, understanding how prevention occurs within social assistance services allows us to understand the complexity in which the violence phenomenon is constituted within the municipal context and what are the obstacles that circumscribe the work of professionals through prevention. For such, a qualitative, documental, and field research was carried out, starting from a historical and critical analysis of the proposed phenomenon. It can be seen, then, that in addition to the perpetuation of violence, we have a precariousness of services due to a policy of omission by the State, which causes a lack of financial resources, worker overload, devaluation of public policies, and a user distancing and, consequently, of children and adolescents who are victims of sexual violence. As much as violence is inherent in this form of social organization, violence prevention is essential to ensure the protection of children and adolescents, requiring the adoption of methodologies that address the needs of children and adolescents.